The Impact of Brand Image on Purchase Intention of The Indonesian National Team Jersey By Erspo - Dzaki Ali Fauzan; Sri Widaningsih (Eduvest - Journal of Universal Studies, 2025)
This study aims to examine the influence of brand image on consumer purchase intention of the Indonesian national football team jersey produced by the Erspo brand. Although Erspo initially faced criticism regarding the design and quality of its products, supporter loyalty remained high. This research uses a quantitative approach with a descriptive method. A total of 100 respondents were selected using the Cochran formula. Data were collected through questionnaires and analyzed using simple linear regression. The results indicate that brand image has a significant effect on the purchase intention of Erspo's Indonesian national team jerseys. The brand image dimensions—strength, favorability, and uniqueness—play an important role in shaping consumer perception and increasing purchase intention. Based on these findings, it is recommended that Erspo continue to strengthen its brand image through design innovation, quality improvement, and effective communication strategies to engage with its consumers.